ECONOMIC REQUIREMENTS AND COMPETENCIES FOR LEADERS IN GENERAL SECONDARY SCHOOLS (Conferencea, 2023)
The transformation of society into a market economy has created the need to radically update the priorities of training specialists in the field of education management. Today, the professional activity of the head of the educational institution is inseparable from the economic context. With the reform of the educational system, the market of educational services is being formed, the status of educational organizations has changed and their economic independence has expanded, which has led to an increase in the responsibility of leaders and an increase in the level of their professional competence.